2023
DOI: 10.1091/mbc.e23-01-0035
|View full text |Cite
|
Sign up to set email alerts
|

p97/VCP drives turnover of SUMOylated centromeric CCAN proteins and CENP-A

Abstract: The centromere is a unique chromatin domain that links sister chromatids and forms the attachment site for spindle microtubules in mitosis. Centromere inheritance is largely DNA sequence-independent but strongly reliant on a self-propagating chromatin domain featuring nucleosomes containing the H3 variant CENP-A. Unlike other histones, CENP-A is maintained with unusually high stability in chromatin. Previously, we have shown that mitotic maintenance of CENP-A and other CCAN proteins is controlled by a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…There has been some evidence that RNF4 is involved, as depletion of RNF4 can rescue centromeric CENP-A levels that are lost in a SENP6 mutant ( Fu et al, 2019 ). However, a recent study could not corroborate this observation ( van den Berg et al, 2023 ). Instead, depletion of RNF4 resulted in a loss of CENP-A rather than suppress excessive SUMOylation, suggesting that RNF4 may play a more direct positive role in maintaining CENP-A.…”
Section: Is There a Role For Sumo-dependent Ubiquitylation Of Centrom...mentioning
confidence: 77%
See 4 more Smart Citations
“…There has been some evidence that RNF4 is involved, as depletion of RNF4 can rescue centromeric CENP-A levels that are lost in a SENP6 mutant ( Fu et al, 2019 ). However, a recent study could not corroborate this observation ( van den Berg et al, 2023 ). Instead, depletion of RNF4 resulted in a loss of CENP-A rather than suppress excessive SUMOylation, suggesting that RNF4 may play a more direct positive role in maintaining CENP-A.…”
Section: Is There a Role For Sumo-dependent Ubiquitylation Of Centrom...mentioning
confidence: 77%
“…However, in contrast to the CCAN components mentioned above, CENP-A itself does not appear to be SUMOylated indicating its levels are controlled via SUMOylation of the downstream CCAN components ( Liebelt et al, 2019 ; Mitra et al, 2020a ). The dynamics of centromere protein loss upon SENP6 depletion showed that while the CCAN proteins CENP-T, CENP-I, CENP-H and CENP-C are rapidly delocalized from the centromere, CENP-A is removed with a delay, indicating its loss is secondary to CCAN protein removal ( van den Berg et al, 2023 ) ( Figure 1C ).…”
Section: The Role Of Sumo In the Control Of Cenp-a Assembly And Maint...mentioning
confidence: 99%
See 3 more Smart Citations